Visualization 5 - Shang Wang (105366) (2025)
In vivo 3D OCT imaging of the mouse oviduct showing the forward embryo movement is driven by the oviduct contraction wave, as a peristaltic pumping process, while the backward embryo movement is driven by the oviduct relaxation, as a suction process, indicating a leaky peristaltic pump. Triangles point at the locations of embryos.